Forensic Accounting and Auditing: Uncovering Financial Frauds - Joshi, Bhumika; Chouhan, Prince (International Journal of Engineering and Management Research, 2024)
The field of forensic accounting combines accounting, auditing, and investigative methods to uncover, examine and deter financial fraud and misconduct. It plays a crucial role in both legal and corporate environments by examining financial records for evidence of fraudulent activity, quantifying damages, and providing litigation support. Forensic Accountant collaborate closely with law enforcement, regulatory agencies and legal teams to examine to white-collar crimes like embezzlement, money laundering, tax evasion and securities fraud. Forensic accounting involves advanced data analysis, fraud detection techniques, and a deep understanding of legal frameworks. It is vital for ensuring financial transparency, protecting organizational integrity, and aiding in the prosecution of financial crimes. As economic crimes become more sophisticated, forensic accounting continues to evolve, adapting to new challenges and technologies in fraud prevention and investigation.